РЕЗУЛЬТАТЫ ОБСЛЕДОВАНИЯ МЕДИЦИНСКИХ РАБОТНИКОВ НА МАРКЕРЫ ВИРУСА ГЕПАТИТА В - Шарова, Алёна Александровна; Иванова, Надежда Всеволодовна; Эсауленко, Елена Владимировна; Данилова, Екатерина Михайловна (Медицина: теория и практика, 2020)